Pengaruh motivasi terhadap perilaku knowledge sharing pegawai di Badan Pusat Statistik wilayah Sulawesi Tengah - Sri Astuti; Tine Silvana Rachmawati; Agus Rusmana (Perpustakaan Universitas Gadjah Mada, 2023)
Introduction. The insufficient level of understanding of statistical indicators is indicated by the low level of knowledge sharing culture among BPS employees in the Central Sulawesi region. In this case, BPS needs to encourage the employees to participate in knowledge sharing activities. Individual's willingness to share knowledge can be influenced by several factors, one of them is motivation. The main objective of this paper is to understand the influence of motivation to employee’s knowledge sharing activities in BPS. A conceptual model is designed based on the Theory of Reasoned Action (TRA). Data Collection Methods. A quantitative-explanatory research method was applied including literature study, data collection, and data analysis. Data Analysis. The study used the structural equation modeling-partial least squares (SEM-PLS) analysis method with a sample of 174 samples. Results and Discussion. Motivation has a positive-significant effect (p-value <0.05) on attitudes (β = 0.713) and employee intentions (β = 0.218). This has implications for employee knowledge sharing behavior (β = 0.758). Motivation and attitude can predict the intention by 42.7%, meanwhile, the intention can predict behavior by 57.5%. Conclusion. To predict the knowledge-sharing behavior of employees, a sufficient motivation is needed to develop positive attitudes and strong intentions in each employee.